EFEKTIVITAS PjBL DAN PEMBELAJARAN KOLABORATIF BERBASIS DIGITAL TERHADAP KEMAMPUAN MENULIS ESAI AKADEMIK - Abdul Haliq; Tuti Wijayanti; Akhiruddin Akhiruddin (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2026)
This study aimed to examine the effectiveness of the PjBL model and Digital-Based Collaborative Learning on students' academic essay writing skills. This study used a quasi-experimental method with a non-equivalent control-group design. The sample consisted of 75 Indonesian Language and Literature Education students divided into three groups: PjBL, digital collaboration, and control. Data were analyzed using ANCOVA and Bonferroni Post Hoc Tests. The results showed that both experimental models were significantly more effective than conventional learning (p<0.01; η²p=0.621). The digital collaborative group obtained the highest N-gain (0.76), followed by the PjBL (0.71) and control groups (0.43). However, the difference between the two experimental models was not statistically significant (p=0.214). Digital-based collaborative learning excelled in motivation and writing organization, whereas PjBL excelled in depth of analysis. This study recommends the integration of both models as a pedagogical innovation for academic essay writing in the digital age.